الكلمات الملايوية ذات أصل عربي في قاموس دايا والاستفادة منها في تعليم اللغة العربية للملايويين المبتدئين - Wilda Elfitria; Husnul Khatimah (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2019)
ABSTRACT The arrival of Islam to the Malay world affected the live of Malay muslims in various aspects, especially in linguistic. Unfortunately, most of Malay people do not know and they do not aware of these words in their language which they communicate everyday. Therefore, this research was based on the analytical descriptive methods that aims to detect Arabic words which have become a part of Malay in the